On differential equations for orthogonal polynomials on the unit circle - Branquinho, A. (2020)
In this paper we characterize sequences of orthogonal polynomials on the unit circle whose corresponding Carathéodory function satisfies a Riccati differential equation with polynomial coefficients, in terms of second order matrix differential equations.